Characterization of a novel carbapenem-hydrolysing β-lactamase OXA-1041 in Escherichia coli. (30th March 2023) - Wu, Shikai; Feng, Yu; Yang, Yongqiang; Zhu, Kairong; Wang, Siyao; Wang, Xinyue; Li, Guo-Bo; Zong, Zhiyong
Abstract: Background: We found a carbapenem-resistant Escherichia coli without known carbapenemase-encoding genes and performed a study to identify the possible new carbapenemase. Methods: The production of carbapenemase was examined using the modified carbapenem inactivation method. The strain was subjected to short- and long-read genome sequencing and the complete genome was obtained by hybrid assembly. The gene encoding a potential new OXA-type carbapenemase was cloned. The enzyme was purified and was then subjected to kinetic assays. Molecular docking analysis of the enzyme was performed using the MOE software suite. Mating experiments were attempted to obtain the plasmid carrying the corresponding gene. Results: We identified and characterized a novel class D carbapenem-hydrolysing β-lactamase, OXA-1041, in a carbapenem-resistant E. coli clinical strain. OXA-1041 had 89.77% (237/264) amino acid identity with OXA-427, a known carbapenemase. By cloning in an E. coli laboratory strain, bla OXA-1041 was found to reduce susceptibility to ertapenem by 16 times (MIC 0.25 versus 0.016 mg/L) and meropenem by four times (MIC 0.06 versus 0.016 mg/L) but did not significantly reduce susceptibility to imipenem and doripenem. Enzyme kinetic measurement of purified OXA-1041 showed that OXA-1041 could hydrolyse ertapenem and meropenem with a turnover number ( k cat )/Michaelis constant ( K M ) of 8.57 and 3.63 mM −1 s −1, respectively. The complete genome contained a single plasmid (223 341 bp, IncF, containing five replicons), which was self-transmissible. bla OXA-1041 was downstream of insertion sequence IS CR1 and there were three tandem copies of IS CR1 - bla OXA-1041 - creD Δ (encoding an envelope protein) on this plasmid. Conclusions: The above findings suggest OXA-1041 is a new plasmid-encoded carbapenemase with preferential activity against ertapenem.